Genomic Analysis of Antibiotics and Secondary Metabolites Biosynthetic Genes Clusters in Bacillus cereus Group (Journal of Biochemistry, Microbiology and Biotechnology, 2024)
Genome mining of the Bacillus cereus group using bioinformatic web resource was conducted to explore the antibiotic potentials of this highly similar group of bacteria. Bacillus cereus group consists of eight closely related Bacillus species, they are gram-positive, spore-forming, aerobic, facultative anaerobic rod-shaped bacteria, and they have low G+C-content when compared with B. subtilis. They include B. cereus, B. anthracis, B. thuringiensis, B. mycoides, B. pseudomycoides B. weihenstephanensis, B. cytotoxicus, B. toyonensis. The genera Bacillus are known to produce antibiotic compounds through biosynthetic gene clusters in their genome which are responsible for the formation of single or multiple natural specialized products. In the present study, whole genome sequences of Eight strains representing each of the B. cereus group bacteria: B. cereus NC7401, B. anthracis  strain STI1, B. thuringiensis  strain TG-5, B. pseudomycoides  strain 219298, B. mycoides  strain Gnyt1, B. cytotoxicus  strain E8.1, B. toyonensis  strain UTDF19-29B and B. weihenstephanensis  strain WSBC 10204 were retrieved from GeneBank database of the National Center For Biotechnology Information (NCBI). The genomic data was analyzed for antibiotic and secondary metabolites biosynthetic gene clusters (BGCs) using antibiotic and secondary metabolites analysis shell version 4.0 (antiSMASH 4.0) pipeline with default parameters. The average size of the genome was approximately 5.035 mb, however, Bacillus weihenstephanensis strain WSBC 10204 has the highest genome size of 5,608,349 bp. The findings of this study identified and reported up to 76 biosynthetic gene clusters in the 8 genomes of the B. cereus group. These clusters were classified into 14 different BGCs, which include 14 RiPP-like, 16 NRPS, 8 NPR-metallophore, 8 betalactone. Comparatively, RRE-containing, Type I polyketides synthase (T1PKS), and Ras-RiPP clusters were scarce across the 8 genomes, and they are only found in the genome of B. cytotoxicus. Similarly, there are 33 (49.25%) unknown clusters for which no known homologous or similar BGCs could be identified, this revealed the potential novelty associated with these clusters.
Keywords: Clusters; Bioinformatics; Genome; Antibiotics; Secondary metabolites